Study of Job Satisfaction of Kazakhstan-based Translators - Poddubnyy, S. (MAQSUT NARIKBAYEV UNIVERSITY School of Liberal Arts. Astana, 2025)
This study explores the job satisfaction of professional translators and interpreters in Kazakhstan, a topic that has received limited empirical attention in the post-Soviet context. Anchored in qualitative methodology, the research investigates how (dis)satisfaction is experienced over time, how it relates to working conditions and institutional practices, and how it influences career trajectories. Drawing on semi-structured interviews with 10 practicing language professionals—including both in-house and freelance translators and interpreters—the study adopts a thematic analysis approach guided by Herzberg’s TwoFactor Theory, the Job Demands-Resources model, and Bourdieu’s Theory of Capital. The findings indicate that job satisfaction is shaped by emotional dynamics, perceived fulfillment, and moments of frustration. Freelancers appreciated flexibility and autonomy but struggled with instability, market saturation, and weak institutional support. In-house professionals often faced limited career progression and bureaucratic constraints but reported more stable incomes. Recognition, fair pay, and belonging emerged as significant drivers of satisfaction, while the lack of protective structures, trade union support, and social recognition undermined long-term professional commitment. Notably, job dissatisfaction did not always lead to immediate career change. Many participants remained attached to the profession due to intrinsic motivation or structural barriers, while others explored adjacent fields such as teaching, content writing, or further academic study. Concerns about artificial intelligence displacing translators — particularly in written domains — also surfaced as a source of anxiety, prompting some to diversify their skills. The study contributes to the understanding of translator/interpreter well-being in non-Western contexts, where market irregularities and institutional neglect pose unique challenges. It also offers practical implications for policymakers, translation agencies, and academic institutions seeking to retain language professionals and improve their work conditions. By giving voice to underrepresented professionals, the research calls for systemic reforms and targeted support to strengthen the sustainability of the translation and interpreting sector in Kazakhstan.
Keywords: translator job satisfaction, interpreter, qualitative study, occupational stress, translation profession, burnout, intrinsic motivators, extrinsic conditions